Brief on the Role of Psychologists in Residential and Home Care Services for Older Adults. (3rd June 2016) - Davison, Tanya E.; Koder, Deborah; Helmes, Edward; Doyle, Colleen; Bhar, Sunil; Mitchell, Leander; Hunter, Carol; Knight, Bob; Pachana, Nancy
Abstract : Objective: This brief examines the evidence that is currently available to inform the provision of psychological services within aged care services, considering both residential care and home care settings. Method: A narrative literature review of the literature evaluating psychological approaches for common conditions in aged care settings was conducted, focusing on the assessment and treatment of common mental health disorders and dementia. Information on the current employment and training of Australian psychologists in geropsychology was also summarised. Results: While further research is required, existing literature provides a clear rationale for the benefit of psychological approaches to address a range of conditions, including the management of dementia. There is only limited research focusing specifically on the home care setting, despite the increasing number of older adults who receive aged care services in their own homes. The current provision of psychological services in Australia is critically low, driven in part by funding limitations. Meanwhile, substantial gaps remain in the training provided to provisional psychologists. Conclusion: A number of key recommendations are made to address the growing need for age‐specific psychological assessments and interventions to be included as part of the delivery of aged care services in this country. Given the continued high prevalence of mental health disorders and dementia within aged care settings, as well as even higher rates of subthreshold conditions, improved access to psychological services for older Australians must become a priority.